Homer like Thucydides? Hobbes and the Translation of the Homeric Poems as an Educational Tool - Catanzaro, Andrea (TTR, 2021)
Thomas Hobbes had a deep and, to some extent, controversial relationship with both the classics and the classical world. At the beginning of his career as a political thinker, for example, he translated from Greek into English the History of the Peloponnesian War by Thucydides. Despite this initial involvement, the philosopher subsequently stopped translating, although, several decades later, in the final period of his life, he decided to return to this activity, translating the Iliad and the Odyssey, apparently for his own amusement, nothing more. However, recent literature has suggested that these works, as in the case of his translation of Thucydides’s work, hid another motive: he wanted to continue spreading his political thought in a period when he no longer able to do it in the usual way because of old age, illness, and, above all, censorship. By offering a comparison of the original Greek texts and Hobbes’s translations, this essay aims to show how he handled the political elements of the Iliad and the Odyssey that did not fit his political theory and ran the risk of undermining his attempt to teach moral and political virtue. It focuses in particular on the political question of overlapping sovereignties, with a view to explaining some systematic uses of translation choices that clearly deviate from the Greek.